BIOTA LAUT SEBAGAI INDIKATOR BIOLOGI DALAM MENENTUKAN STATUS PENCEMARAN PERAIRAN TULEHU KECAMATAN SALAHUTU MALUKU TENGAH - ALLIFAH AF, ASYIK NUR; AF, ASYIK NUR ALLIFAH; NATSIR, NUR ALIM (Biosel Biology Science and Education, 2022)
Tulehu State Beach is a bay area which has quite busy activities because there is a port which is the sea gate of Tulehu State. This is suspected to have caused the coastal area of Tulehu to experience a decline in water quality and was polluted. Marine biota is an indicator of the quality of coastal waters that can provide information on the state of these waters in good condition or not. This study aims to determine the number and types of marine biota on the coast of Tulehu State Beach, Salahutu District, Central Maluku Regency and the pollution status of the coast of Tulehu State Beach based on marine biota as bioindicators. This research was conducted in February 2020 - March 2020. The method used in determining the location is purposive sampling which is divided into 3 stations based on the representation of different characteristics in the study location. Data analysis uses the Shannon-Wiener Diversity Index, Uniformity Index and Dominance Index. The results showed that there were 6 marine biota families, namely Littorinidae, Potamididae, Nerithidae, Muricidae, Portunidae and Pectinidae with 592 individuals. The status of pollution of the coast of the State of Tulehu shows polluted, unstable communities and there are species that dominate.Keywords: Pollution; Marine biota; Diversity; Bioindicator